DISPERSION OF SCHEMES IN THE PUBLIC SECTOR LABOR LIMIT AS SALARIES APPROVED AND BENEFITS OF TEACHERS OF UNMSM - Avelino Sánchez, Esteban Marino (2013)
The problem is the repeated failure of the Peruvian government of its own law on remunerative amounts of magistrates of the judiciary and especially of teachers of public universities, which creates discomfort, indeed by the parallel application of labor regimes in the private sector, but is administered as public and private costs. The monthly remuneration received, freely available, of Congress in the last 15 years was higher than S /. 23 000.00, remuneration of senior judges and trial is less than what is stated in Article 186 of the Law on the Judiciary, the approved remuneration of teachers in the San Marcos National University - UNMSM represents less than a third income of the judges of the levels with which was approved. The social benefit amounts calculated with the rules of Congress Rules contrast with the amounts calculated with the rules of the Legislative Decree 276, the differences are abysmal, the supreme judges CTS 396 times compared to the CTS primary teachers because there is no clear human resources policy and objectives in line with national economic and social development.